George Fox the Younger: an early Quaker conservative? - McArthur, Euan David (Quaker studies, 2024)
Quakerism is conventionally viewed as a politically radical movement at its foundations. This thesis has been challenged recently, but the problem remains that early Quakers provided little justification for a politics comfortable with established social and political hierarchies. This article proposes that early Quakerism’s ‘incoherence’, a feature which intellectual historians are often alert to within political texts and movements, was patched up by the efforts of George Fox the Younger (d.1661), a previously little studied Friend. Scholars have often discounted or misinterpreted Fox’s work, but it can provide a key to understanding political boundaries which the movement respected in practice. This essay establishes his thought’s representative quality, despite the relative singularity of his voice. This may provide a hermeneutic for other studies of Quakerism and intellectual history; and some reflections upon Fox’s abiding normative importance are made.